III—The Wonder Of Signs. Issue 1 (12th January 2021) - Haddock, Adrian
Abstract: Anscombe (1956 ) raises a difficulty for the very idea of quotation. Davidson (1979) seeks to dissolve this difficulty. But the difficulty is real. And its lesson is that, in quotation, language takes itself as its topic in a non-objectifying manner. The idea of a non-objectifying manner of being a topic is crucial, not merely for understanding quotation, but for understanding the distinctive form of sensory consciousness in which language is perceived.